Understanding the onset of oscillatory swimming in microchannels. Issue 21 (17th May 2016) - de Graaf, Joost; Mathijssen, Arnold J. T. M.; Fabritius, Marc; Menke, Henri; Holm, Christian; Shendruk, Tyler N.
Abstract : Hydrodynamic interactions beyond the principal dipole are crucial to understand the formation of the oscillatory trajectories of microswimmers under confinement. Abstract : Self-propelled colloids (swimmers) in confining geometries follow trajectories determined by hydrodynamic interactions with the bounding surfaces. However, typically these interactions are ignored or truncated to the lowest order. We demonstrate that higher-order hydrodynamic moments cause rod-like swimmers to follow oscillatory trajectories in quiescent fluid between two parallel plates, using a combination of lattice-Boltzmann simulations and far-field calculations. This behavior occurs even far from the confining walls and does not require lubrication results. We show that a swimmer's hydrodynamic quadrupole moment is crucial to the onset of the oscillatory trajectories. This insight allows us to develop a simple model for the dynamics near the channel center based on these higher hydrodynamic moments, and suggests opportunities for trajectory-based experimental characterization of swimmers' hydrodynamic properties.